2023
DOI: 10.1039/d3dt02512h
|View full text |Cite
|
Sign up to set email alerts
|

Immobilizing ultrasmall Pt nanocrystals on 3D interweaving BCN nanosheet-graphene networks enables efficient methanol oxidation reaction

Binfeng Shen,
Yujie Wei,
Pengyun Sun
et al.

Abstract: A stereo-assembly strategy is developed for the bottom-up construction of ultrasmall Pt immobilized on 3D interweaving B-doped g-C3N4 nanosheet-graphene networks, which exhibit exceptional electrocatalytic methanol oxidation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The mass and specific activities of different Pt/CNH-G as well as reference catalysts were next investigated by CV in a mixed solution containing 0.5 M H 2 SO 4 and 1 M CH 3 OH. As depicted in Figures 5(d)-5(f), all recorded CV curves show a significant positive current peak near 0.7 V, corresponding to the oxidation of methanol molecules on the electrode surface, while the reverse current peak near 0.5 V is attributed to the oxidation of CO-like by-products [40,41]. Consistent with the aforementioned ECSA results, the Pt/(CNH) 5 -G 5 catalyst exhibits a high mass activity of 1626.0 mA mg -1 , which is significantly better than that of Pt/(CNH) 3 -G 7 (1126.5 mA mg -1 ), Pt/(CNH) 7 -G 3 (1028.3 mA mg -1 ), and Pt/(CNH) 1 -G 9 (829.0 mA mg -1 ), verifying that a proper CNH/G ratio can give full play to the electrocatalytic functions of Pt.…”
Section: Resultsmentioning
confidence: 86%
“…The mass and specific activities of different Pt/CNH-G as well as reference catalysts were next investigated by CV in a mixed solution containing 0.5 M H 2 SO 4 and 1 M CH 3 OH. As depicted in Figures 5(d)-5(f), all recorded CV curves show a significant positive current peak near 0.7 V, corresponding to the oxidation of methanol molecules on the electrode surface, while the reverse current peak near 0.5 V is attributed to the oxidation of CO-like by-products [40,41]. Consistent with the aforementioned ECSA results, the Pt/(CNH) 5 -G 5 catalyst exhibits a high mass activity of 1626.0 mA mg -1 , which is significantly better than that of Pt/(CNH) 3 -G 7 (1126.5 mA mg -1 ), Pt/(CNH) 7 -G 3 (1028.3 mA mg -1 ), and Pt/(CNH) 1 -G 9 (829.0 mA mg -1 ), verifying that a proper CNH/G ratio can give full play to the electrocatalytic functions of Pt.…”
Section: Resultsmentioning
confidence: 86%
“…22 Additionally, their three-dimensional (3D) integration of Pt nanocrystals into BCN-G networks showcased exceptional electrochemical properties and resilience in methanol electrooxidation, surpassing conventional Pt catalysts. 23 These advancements indicate promising directions for catalyst development across various applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, their research on Pd nanocrystals grown on MXene and graphene oxide revealed an electrode with significantly reduced charge-transfer resistance . Additionally, their three-dimensional (3D) integration of Pt nanocrystals into BCN-G networks showcased exceptional electrochemical properties and resilience in methanol electrooxidation, surpassing conventional Pt catalysts . These advancements indicate promising directions for catalyst development across various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, nanocarbon-based electrocatalysts usually exhibit reaggregation or restacking due to van der Waals forces in practical applications, and accordingly, their electrocatalytic performance shows a sharp decline. 37,38 In addition, most carbon nanomaterials lack efficient porous channels in their structures; thus, electrolyte transfer to the underlying catalytically active sites is difficult because reactant diffusion occurs only along the basal plane, and consequently, the overall catalytic efficiency of the nanomaterials decreases. 39,40 In recent years, the development of porous carbon nanoarchitectures as advanced matrices for dispersing noblemetal nanocrystals has gradually revolutionized the field of electrocatalysis and electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the aforementioned shortcomings, combining noble metals with appropriate matrices is recognized as an intelligent strategy to ameliorate the electrocatalytic performance of hybrid catalysts as well as effectively reduce the dosage of noble-metal components. , Among the known diverse supporting materials, carbon nanomaterials, such as carbon nanofibers (CNFs), carbon nanotubes (CNTs), and graphene, have attracted considerable and persistent attention owing to their intriguing physicochemical characteristics and catalytic functionality: (i) carbon networks with large specific surface areas are ideal platforms for nucleating and growing noble-metal nanocrystals with high dispersibility; (ii) owing to the tunable surface chemistry of carbon nanomaterials, electronic structures of noble-metal atoms can be optimized via strong interfacial interactions; (iii) because of the exceptional chemical stability of carbon supports, noble metal-based catalytic systems can maintain their structural integrity even under harsh electrocatalytic condition; and (iv) the excellent electrical conductivity of carbon nanomaterials allows abundant unimpeded charge-transfer pathways to increase the number of the triple-phase boundaries. Despite these advantages, nanocarbon-based electrocatalysts usually exhibit reaggregation or restacking due to van der Waals forces in practical applications, and accordingly, their electrocatalytic performance shows a sharp decline. , In addition, most carbon nanomaterials lack efficient porous channels in their structures; thus, electrolyte transfer to the underlying catalytically active sites is difficult because reactant diffusion occurs only along the basal plane, and consequently, the overall catalytic efficiency of the nanomaterials decreases. , …”
Section: Introductionmentioning
confidence: 99%